Isolation and Screening of Bacillus subtilis from Soil for Amylase Production - Madika, A.; Ameh, J.B.; Machido, D.A. (UMYU Journal of Microbiology Research)
This study was aimed at isolating Bacillus subtilis from soil and screening the isolates for amylase production. A total of fifteen (15) soil samples, five each from botanical garden, refuse dump sites and flower beds were collected and subjected to cultural isolation followed by biochemical and microgen identification. The isolates of B. subtilis were then screened for amylase production using starch agar plate method. Nine (9) isolates were confirmed to be Bacillus subtilis with percentage occurrence of 80% from refuse dump sites and botanical  garden and 20% from flower bed. All the B. subtilis isolates demonstrated amylase production ability with isolate RD4 from refuse dump sites having the highest diameter of zone of starch hydrolysis (29mm). Bacillus subtilis can readily be isolated from various soil types with frequency of 80% in soils from garden and refuse dumps and 20% from flower bed. All the B. subtilis isolates demonstrated the potential for amylase production. This preliminary study could provide information on the isolation of B. subtilis from various soil types for the production of amylase.